Ecologically clean evaporation-condensation method application for obtaining of electrical contacts based on copper composite materials - Grechanuyk, Vira G.; Matsenko, Olexandra V. (ІТГІП, 2018)
In this paper is considered the electron-beam technology on new materials creation, including copper and its alloys, as one of the most promising directions of modern electrometallurgy. The formation process of condensed composite materials (CCM) using this technology is absolutely environmentally clean, because it occurs in a vacuum, in addition, similar materials are obtained in a single technological cycle, what is economically profitable. It is shown that this method was used for the first time to obtain structural composite materials Cu-Mo, Cu-W, Cu-Cr (massive sheet condensates weighting up to 30 kg separated from the substrate), which were used for electrical contacts and electrodes. The most industrial applications found the condensed from the vapor phase CM of Cu-Zr-Y-Mo and Cu-Cr-Zr-Y-Mo systems for discontinuous electrical contacts. The mechanical properties of materials of Cu-Zr-Y-Mo system have been studied and it is shown that these materials are characterized by a sufficiently high electrical conductivity, hardness, strength and satisfactory plasticity, and mostly allows to refuse from silver-containing contacts, since they are not inferior, and in some cases exceed them for their operational reliability.
Keywords: method; evaporation-condensation; copper; composite materials; electrical contacts